Effect of nitrous oxide use on external cephalic version success rate; a systematic review and meta-analysis. (12th December 2022) - Massalha, Manal; Izhaki, Ido; Iskander, Rula; Salim, Raed
Abstract: Introduction: Several adjuvant interventions have been evaluated for improving the success rate of the external cephalic version (ECV) and reducing the rate of cesarean delivery (CD). Evidence regarding the effect of Nitrous oxide is limited to a small number of participants with inconsistent results on pain score and success rate. This study aims to examine the effect of inhaled nitrous oxide on the success rate and pain score for women undergoing ECV. Material and methods: Survey on ECV reports from inception till June 2020 were made from MEDLINE, EMBASE, PubMed, Ovid Medline, ClinicalTrials.gov, the Cochrane Library and Google Scholars. Peer-review studies that examined the success rate of ECV from the application of nitrous oxide during ECV attempts compared with or without the use of other analgesic agents were obtained. The study population comprising women with singleton pregnancies having a non-vertex presentation at least 36 weeks, were categorized into one of two treatment groups: ECV attempt with nitrous oxide (nitrous oxide group) and ECV attempt with or without another analgesia (control group). The primary outcome was the ECV success rate, defined by conversion to vertex-presentation following the procedure. The secondary outcomes were pain scores during ECV attempt and CD rate. The study quality scores were evaluated as a source of heterogeneity by fitting meta-regression models to the individual study effect sizes. Results: Of the 26 records identified, two randomized trials and one prospective cohort study (720 women; 434 in the nitrous oxide group and 286 controls) were deemed adequate for meta-analysis. ECV success rate did not differ significantly between the nitrous oxide group and the control group ( p  = .825; OR 1.036; 95% CI, 0.756, 1.419). In addition, the use of nitrous oxide did not affect pain scores during ECV attempt ( p  = .457; OR 0.759; 95% CI, −1.240, 2.759) and there was no difference in the incidence of CD as well ( p  = .943; OR 1.013; 95% CI, 0.703, 1.46). Conclusion: The use of nitrous oxide during ECV attempts was not associated with an increase in ECV success rate and does not affect pain scores. PROSPERO Registration No. CRD42020197933